DISIPLIN PEGAWAI DALAM MEMBERIKAN PELAYANAN PADA KANTOR SAMSAT KOTA KENDARI - Arie R, Meylinda; Justawan, Justawan; Darpin, Darpin (Universitas Halu Oleo, 2019)
The purpose of this research is to know the discipline of the employee in giving service at One Roof System office Kendari city. The population in this research is all employee in Region Technical Implement Unit office of One Roof System Kendari city, there are 40 peoples. Consider the amount of relative population is little only 40 peoples, therefore the technique to get a sample is using sampling total method that determines the population directly as the respondent of research. Besides determining respondent, the writer determines informant also as a comparison that is Â The Head Of Region Technical Implement Unit office of One Roof System Kendari city and The Head Of Subdivision Of Administrative Affair Region Technical Implement Unit office of One Roof System Kendari city. The result of this research is showing discipline of an employee at Region Technical Implement Unit of One Roof System Kendari city is quite good, in other words, there are many employees are discipline less in his or her occupation. Â Besides, application of discipline to increase the service at Region Technical Implement Unit of One Roof System Kendari city, consider that is not good based on reaction of respondent towards five indicators such as simplicity, openness, clarity, certainty and time accuracy, then it can be said the purpose of organization is less to reach its purpose if discipline in giving service is not satisfied. Because by high discipline can make the performance of an employee is good more.Â